Association of a SNP in SLC35F3 Gene with the Risk of Hypertension in a Chinese Han Population - Zang, Xiao-Li; Han, Wei-Qing; Yang, Feng-Ping; Ji, Kai-Da; Wang, Ji-Guang; Gao, Ping-Jin; He, Guang; Wu, Sheng-Nan (Frontiers in Genetics, 2016)
A recent study suggested that SLC35F3 which encoded a thiamine transporter was a new candidate gene for hypertension. The goal of this study was to investigate the association between the single nucleotide polymorphisms (SNPs) in the SLC35F3 gene and hypertension in a Chinese population. Sanger sequencing was performed in 93 samples to find SNPs in coding regions and intron-exon boundaries in the SLC35F3 gene. We found eight genetic variants in the coding regions of SLC35F3 and subsequently genotyped a non-synonymous variant rs34032258 (C>G) in 1060 hypertension patients and 1467 controls. After adjusting for age and gender, multivariate analysis of covariance showed that the variant was associated with hypertensive traits. In detail, diastolic blood pressure (DBP) was 8 mmHg higher, blood urea nitrogen (BUN) was 12 mmol/L higher, and creatinine (Cr) was 15 mmol/L lower in G/G group compared with C/C group (P =0.007; 0.012 and 0.029 respectively). Further study suggested that C/G+G/G had higher DBP than C/C genotype in those whose DBP ≥ 90 mmHg (98.02 mmHg vs. 94.04 mmHg, P=0.021). No significant difference has been found in systolic blood pressure (SBP) between different genotypes. Additionally, in the subgroup of obesity, allele distribution of this variant has shown significant difference between hypertensive patients and normotensive controls (P=0.018). In conclusion, we found that the rs34032258 in the SLC35F3 gene was associated with high blood pressure and may increase the risk of hypertension. The new hypertension-susceptibility locus may involve in the pathogenesis of hypertension and indicate some novel treatment implications.